Colon cancer–derived conditioned medium induces differentiation of THP-1 monocytes into a mixed population of M1/M2 cells. Issue 9 (August 2018) - Sawa-Wejksza, Katarzyna; Dudek, Adrianna; Lemieszek, Marta; Kaławaj, Katarzyna; Kandefer-Szerszeń, Martyna
Macrophages play an important role in the immune response and in the maintenance of tissue homeostasis. It is well known that many tumors recruit monocytes from circulation and influence their differentiation, mainly into suppressive M2-like subsets. Since there are contradictory data concerning the importance of macrophages for colon cancer progression, we used in our experiments four colon cancer cell lines representing different stages of tumor development (HT29, LS180, SW948, SW620). An acute monocytic leukemia cell line THP-1 was used as a human model of monocytes. Our work revealed that conditioned medium from the tumor cell lines induced activation and differentiation of THP-1 cells. The changes involved increased expression of CD68, a macrophage differentiation marker. Moreover, we also observed increased expression of CD206 and CD163, which are widely considered as markers of tumor-associated macrophages. The tumor-derived conditioned medium decreased the proliferation of THP-1 cells and blocked their cell cycle at the G1 stage. The tumor-conditioned medium also upregulated the production of several cytokines and chemokines characteristic of both M1 and M2 subsets and induced the expression of important pro-angiogenic factors, vascular endothelial growth factor, and matrix metalloproteinase-9 in THP-1 cells. Moreover, the tumor-conditioned medium induced the expression of galectin-3, which is implicated in malignant transformation, and indoleamine 2, 3-dioxygenase, that is, a key enzyme of the kynurenine pathway. Our data suggest that tumor cells can actively influence the phenotype of monocytes and switch their differentiation into a population of non-adherent mixed M1 and M2 cells. These preliminary studies suggest that colon cancer cells produce soluble factors that influence monocyte differentiation, most probably into suppressive subsets. These data provide a better understanding of the influence of colon cancer on polarization of monocytes.